An Unclear Question: Who Owns Patient Information? A Kantian Take on the Concept of Datenherrschaft - Jani Koskinen; Kai Kimppa (My University, 2025)
Abstract. Patient information systems are critical instruments in modern healthcare; thus, modern healthcare systems cannot function properly without them. While there are countless varieties of information systems used in healthcare, there is one overarching commonality among them – they all contain information about patients. Different groups involved in healthcare have an interest in patients’ information for different reasons. However, in many countries, it remains unclear who exactly owns the data. This issue thus needs to be resolved. As ethics is critical in determining the justifiable owner of patient information, any legislative solution to competing interests ought to be ethically well justified. In this paper, we argue that an ethically acceptable formulation of the ownership of patient data has already been suggested and that it can be further justified also through the Kantian tradition.
Technology and Intimacy: Choice or Coercion